Combination of concurrent targeted and immune-therapy with nivolumab and cetuximab: new perspectives for squamous cell carcinoma treatment - A. M. Mudunov; A. V. Ignatova; A. S. Morozova; S. O. Podvyaznikov; Yu. V. Alymov (Опухоли головы и шеи, 2020)
Head and neck squamous cell carcinoma (HNSCC) is the most common cancer among head and neck malignancies and causes of cancer death. More than 50 % of patiens have relapses within first 3 years after treatment, with median survival less than 6 months. Cetuximab is the first targeted agent for HNSCC, is considered as alternative regiment in case of intolerance to platinum-based chemotherapy, and also can activate an antigenspecific T-cell immunity in head and neck cancer patients. Nivolumab is a check-point inhibitor, that improves overall survival of patients with advanced recurrent/metastatic HNSCC, due to the CheckMate-141 study results. The results of phase II study сoncurrent cetuximab and nivolumab in patients with recurrent and/or metastatic HNSCC showed a benefit for patients without prior check-point inhibitor exposure and overall well tolerated. Thus, we have 6 cases of HNSCC, treated with combination of nivolumab and cetuximab, resulted in durable (12 months) partial response or stabilization without severe adverse events. In our study, all 6 patients had prior check-point inhibitor exposure with nivolumab. Cetuximab was added to a treatment protocol after evidence-based progression during check-point inhibitor therapy. We demonstrate a case report of recurrent locally advanced HNSCC, treated with combination of nivolumab and cetuximab and resulted in stabilization. Only 1 patient had a progression after concurrent targeted and immune-therapy with nivolumab and cetuximab. New combination was well tolerated without severe adverse events. To our opinion, first results are challenging and we believe in great perspectives of comprehensive molecular profiling and combination of targeted and immune-therapy for better results.